Kinerja Aparatur Sipil Negara di Universitas Brawijaya (Studi Kasus pada Sub Bagian Tenaga Kependidikan) - Azis, Abdul (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
The main objective of this research is to describe how the performance of the state civil apparatus (ASN) in the sub-section of the education staff, the headquarters of the University of Brawijaya, and identify the inhibiting factors and drivers of performance. This study uses five performance indicators, namely: (a) quantity, (b) quality, (c) effectiveness, (d) timeliness, and (e) independence. The study was conducted using descriptive qualitative methods. The research location is the subsection of education staff, staffing, Universitas Brawijaya head office. Data obtained through interviews, environmental observations and documentation. Respondents in this study were all ASNs in the sub-section of education staff and several other related ASNs. The results of this study indicate that: (a) the quantity of performanceagainst the target is very good; (b) the quality of good performance; (c) the effectiveness is quite good; (d) the accuracy of service in completing the task is not good; and (5) independence is not good. Factors that influence performance are of two sources, namely: from within the ASN itself and from the work environment of the ASN.